2015
DOI: 10.1002/2014ja020584
|View full text |Cite
|
Sign up to set email alerts
|

Unusual depletion of OI 630.0 nm dayglow and simultaneous mesopause heating during the penetration of interplanetary electric field over dip equator

Abstract: Evidence for simultaneous changes in the thermosphere and mesopause associated with penetration electric fields using the OI 630.0 nm and OH (8, 3) dayglow measurements are presented. An unusual decrease in the thermospheric OI 630.0 nm dayglow and an intense heating (~30 K) at OH emission altitudes over a magnetic dip equatorial station, Trivandrum, India, were observed on 9 April 2006, coincident with the penetration of a noontime westward interplanetary electric field. The Sounding of the Atmosphere using B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The unusual depletion of this optical emission observed during the period~14:45-16:30 IST is not new. In fact, such drastic changes in the equatorial dayglow in conjunction with a number of penetration events and the corresponding physical mechanism have already been reported (Sumod et al, 2015). The observed depletion in the present case could be associated with the eastward PPEF which enhanced the plasma fountain over the equator due to the increased upward E Â B drift.…”
Section: Response Of the Equatorial Ionospheresupporting
confidence: 73%
See 1 more Smart Citation
“…The unusual depletion of this optical emission observed during the period~14:45-16:30 IST is not new. In fact, such drastic changes in the equatorial dayglow in conjunction with a number of penetration events and the corresponding physical mechanism have already been reported (Sumod et al, 2015). The observed depletion in the present case could be associated with the eastward PPEF which enhanced the plasma fountain over the equator due to the increased upward E Â B drift.…”
Section: Response Of the Equatorial Ionospheresupporting
confidence: 73%
“…Sumod et al (2014) have reported prompt and delayed effects of these optical emissions over a dip equatorial station, associated with solar flares of different ranks. Very recently, concurrent variability of the equatorial ionosphere and mesopause in the context of a number of penetration events has also been presented in the literature (Sumod et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Following this reduction, the dayglow intensity increased concomitantly with the X-ray/EUV radiations during the flare event. This increase in dayglow, which showed a peak at ~ 15:30 IST, is attributed to the increased O( 1 D) production during the flare time due to all the three production mechanisms, viz, photo-electron impact of O, photo-dissociation of O 2 and dissociative recombination of O 2 + , as discussed in Sumod et al (2015). However, the dayglow did not show any appreciable signature associated with the secondary peak in the EUV flux.…”
Section: Response Of Equatorial Thermospherementioning
confidence: 79%
“…In this context, the ground-based neutral thermospheric OI 630.0 nm dayglow emissions are ideal for investigating such ephemeral events like flare, as they emanate from the altitudes, where maximum EUV absorption takes place. These dayglow measurements over Trivandrum, in recent years, have brought out many significant results pertaining to various aspects of coupling processes in the equatorial upper atmosphere (e.g., Sumod et al 2011aSumod et al , b, 2012Sumod et al , 2014Sumod et al , 2015. In the present work, an attempt is made to investigate the effects of X3.8 solar flare, which occurred on January 17, 2005, over equatorial ionosphere-thermosphere system, using combined high cadence measurements of thermospheric OI 630.0 nm dayglow, GPS-measured ionospheric Total Electron Content (TEC) and the strength of Equatorial Electrojet (EEJ).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the response of the neutral thermosphere to the PPEF events, an enhancement in thermospheric OI 630.0-nm dayglow emission over the low-latitude region has been reported by Chakrabarty et al (2005). On the other hand, a depletion of OI 630.0-nm dayglow emission over the dip equator has been observed by Sumod et al (2015). During the evening hours an unusual enhancement in PRE has also been observed during an eastward PPEF, which resulted in the formation of ESF and signal scintillations on satellite communication systems (Basu, Basu, Valladares, et al, 2001;Basu, Basu, Groves, et al, 2001).…”
Section: Introductionmentioning
confidence: 97%